2020
DOI: 10.1016/j.stemcr.2020.03.027
|View full text |Cite
|
Sign up to set email alerts
|

Single-Cell Analysis Reveals Partial Reactivation of X Chromosome instead of Chromosome-wide Dampening in Naive Human Pluripotent Stem Cells

Abstract: Recently, a unique form of X chromosome dosage compensation has been demonstrated in human preimplantation embryos, which happens through the dampening of X-linked gene expression from both X chromosomes. Subsequently, X chromosome dampening has also been demonstrated in female human pluripotent stem cells (hPSCs) during the transition from primed to naive state. However, the existence of dampened X chromosomes in both embryos and hPSCs remains controversial. Specifically, in preimplantation embryos it has bee… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 23 publications
2
22
0
Order By: Relevance
“…There is also gain of active Pol II and DNA demethylation [ 43 , 179 , 200 , 209 ]. One study reported H3K27me3 enrichment [ 200 ] and other studies reported little or no H3K27me3 enrichment under the XIST RNA foci in naive human pluripotent stem cells [ 180 , 210 ]. Finally, the transition also induces dampening of X-linked gene expression [ 200 ], reminiscent of early human embryos [ 183 ].…”
Section: Xcr Following Reprogramming To Human Naive Pluripotencymentioning
confidence: 99%
See 1 more Smart Citation
“…There is also gain of active Pol II and DNA demethylation [ 43 , 179 , 200 , 209 ]. One study reported H3K27me3 enrichment [ 200 ] and other studies reported little or no H3K27me3 enrichment under the XIST RNA foci in naive human pluripotent stem cells [ 180 , 210 ]. Finally, the transition also induces dampening of X-linked gene expression [ 200 ], reminiscent of early human embryos [ 183 ].…”
Section: Xcr Following Reprogramming To Human Naive Pluripotencymentioning
confidence: 99%
“…Moreover, H3K27me3 enrichment is not sufficient for silencing gene expression like in mouse [ 76 , 200 ]. Recently, another study proposed that dampening corresponds to erasure of XCU [ 210 ]. XIST reactivation is also preceded by a stage with XIST silencing [ 200 ].…”
Section: Xcr Following Reprogramming To Human Naive Pluripotencymentioning
confidence: 99%
“…Several questions arise from this pioneering work in hPGCs to better understand what 'dampening' precisely relates to. First, it is important to bear in mind that conclusions about dampening are essentially based on scRNA-seq data analysis, which may lead to contradictory interpretations due to analyses pipelines 10,11 . As illustrated in Fig.…”
Section: Fig 1 | Models For X-chromosome Activity Control During Hummentioning
confidence: 99%
“…Down the line, several independent studies came out both in supporting and refuting Ohno's hypothesis [10][11][12][13][14][15][16][17][18][19]. Although, Ohno's hypothesis is still contested, recent studies by us and others have shown the presence of upregulated active-X chromosome (X2a) in different cell types in vivo and in vitro [20]. However, the dynamics of X-chromosome upregulation (XCU) during early development remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%